The potential impact of introducing a cost tool to facilitate cost-of-care conversations in routine OB care: Lessons from the CONTINUE pilot study - Veronica Fitzpatrick; Kim Erwin; Anne Rivelli; Maureen Shields; Leah Delfinado; Marie Cabiya; Karen Wennerberg (Elsevier, 2023)
Objective: The objective of the CONTINUE study is to gather preliminary data on the potential impact of implementing a "Cost Tool" in routine obstetrics (OB) care. It is hypothesized that by providing prenatal patients with an ability to forecast their care plan, they would be better able to anticipate and plan for the costs associated with their prenatal care. Methods: Pilot data from interviews and surveys were collected from 71 prenatal patients across three clinics throughout Chicago, IL. Results: As compared to privately insured prenatal patients, prenatal patients with public insurance reported the most benefit in Cost Tool use. Specifically, that the Cost Tool helped to navigate insurance more effectively (OR 4.49, p=0.0254), see the ''Big Picture'' and link it to the family budget (OR 4.25, p=0.0099), and make the financial tradeoffs needed to get through pregnancy (OR 5.50, p=0.0305). Conclusion: The CONTINUE study provides preliminary signals of the Cost Tool's potential to help publicly insured prenatal patients better navigate the costs associated with their care plan. Innovations: The CONTINUE study contributes valuable preliminary data about the utility of a cost tool in routine OB care, especially as it may benefit low-income prenatal patients navigate prenatal care better.